Effective remediation programs for vulnerable students to overcome learning loss - Madelon Jacobs; Carla Haelermans; Martijn Meeter (PLoS ONE, 2025)
In March 2020, the world was forced to cope with the COVID-19 pandemic, and as a result, schools in many countries closed to minimize the spread of the coronavirus. Students were required to shift to online learning from home. Not long after that, research showed that students in the first half-year of the COVID-19 pandemic experienced extensive learning losses compared to peers from previous cohorts. An important question is whether these losses can be remediated or lead to permanently lower attainment for a generation of students. Here, we study the effectiveness of a nationwide attempt at remediation in the Netherlands, where the government provided funds for schools to proactively minimize the detrimental effects of the COVID-19 pandemic. Unique standardized test score data of over 66,000 Dutch primary school students were combined with information about the various remediation programs employed uniquely in each school to investigate to what extent remediation occurred. Applying a Difference-in-Differences design, we find an overall statistically significant and meaningful increase in the achievement of vulnerable students after participation in remediation programs (+ 0.05 SD). Participating students had a higher increase in test scores compared to non-participants within the same school, and the inequality between the latter and former has slightly been reduced (~10%). Remediation programs offering individual support to students or in small groups, and with a sole emphasis on cognitive skill development, were most successful.